Nitrogen Fixation - Cid Rigobelo, Everlon; Pereira Serra, Ademar (Biochemistry, 2020)
Biological nitrogen fixation (BNF), the process by which gaseous N2 is converted into ammonia (NH3) via the enzyme nitrogenase, is crucial for the availability of nitrogen (N) in the terrestrial ecosystem. Some bacteria have the remarkable capacity to fix atmospheric nitrogen to ammonia under ambient conditions, a reaction only mimicked on an industrial scale by a chemical process. This microbiological process converts atmospheric nitrogen into a plant-usable form, thus decreasing the need to use chemical fertilizers in crop production. Chapters in this volume cover different aspects of this fantastic phenomenon, including biofertilizer, organic nitrogen in agricultural systems, nitrogen fertilization for sustainable crop production, and others. This book is designed for researchers, students and general readers.